Investigation on bonding between aggregates and asphalt binder containing warm mix additives - Pratap Wagh V.; Sukhija M.; Gupta A. (My University, 2025)
Increased moisture susceptibility has been identified as one of the potential failures for warm-mix asphalt (WMA). In order to critically understand the moisture damage mechanism, the evaluation of bond strength between aggregate and asphalt binder holds significant importance. The bonding mechanism can be easily explained by Pneumatic Adhesion Test (PAT). This study evaluated the bond between various aggregates and warm mix (WM) modified asphalt binders using PAT. Five aggregates, two base binders, and four WM additives with varying dosages have been selected for the present experimental study. The objective is to identify the relative contribution of these factors towards the development of bond strength and their consequence against moisture damage. Bond strength was evaluated in terms of the pull-off tensile strength (POTS), whereas moisture susceptibility was determined using the bond strength ratio (BSR) parameter. Results showed that the bonding between aggregate and asphalt binder relies on the aggregate type, base binder, WM additives and their dosages. Since PAT was carried out on both wet and dry-conditioned samples, it was found that the conditioning state (wet and dry) also affects the interfacial bonding of the asphalt-aggregate matrix. Wet-conditioned samples tend to exhibit lower POTS values than dry-conditioned samples. The BSR values were found to be different for various aggregate-asphalt binder combinations. The minimum BSR was found to be 0.82 for a moisture-resistant asphalt mixture. © 2023 Elsevier Ltd